Media Dualism in Indonesia's Coverage of the Sexual Violence Bill - Krisdinanto, Nanang; Apul, Merlina Maria Barbara; Hartiana, Theresia Intan (Program Studi Ilmu Komunikasi, 2023)
This research is motivated by two primary factors. First, the emergence of alternative news media can be considered as a counterbalance to the professional news media with their various biases. The second pertains to the protracted legislative process of the Sexual Violence Bill (RUU TPKS) before its eventual enactment. The objective of this study is to see examine these two media categories frame the protracted struggle in the legislative process of the TPKS Bill, given that framing reflects the media's perspective, which subsequently influence the audience's understanding of the issue. The subjects of this research are news related to the TPKS Bill as presented by both professional and alternative media in Indonesia. This research employs a qualitative approach in conjunction with the framing method developed by Robert Entman. This study’s findings reveal diametrical contrast in the frames adopted by professional and alternative media in reporting the TPKS Bill. Professional media constructs a frame that characterizes the protracted discussion of the TPKS Bill in the DPR as a technical-procedural problem. In contrast, alternative media framed it as a result of the DPR’s failure or lack of commitment to protect victims of sexual violence.